ADOPTION OF INNOVATION OF MEMBERS OF FARMING GROUPS IN THE USE OF ZPT( GROWTH REGULATORY SUBSTANCE ) IN TREATMENT OF RICE SEEDS (Oryza Sativa L.) IN CILAKU DISTRICT, CIANJUR DISTRICT, WEST JAVA PROVINCE - Rahmad Dyanto; Kusmiyati Kusmiyati; Dwiwanti Sulistyowati (Jurnal Inovasi Penelitian, 2020)
Behavioral District has the potential of plants for the availability of food plants and various spices to be developed more broadly in order to increase productivity, especially rice food plants. So this study aims to describe the adoption of farmer group members, analyze the factors associated with the adoption of innovations, and look for strategies in increasing the adoption of farmer group members' innovations. This research was conducted in Behavioral District of Cianjur Regency. The sample of this study were 55 farmers who tried paddy fields taken with the technique of Random Sampling. The independent variables include independent factors including internal factors, namely age, level of education, length of farming, and land area external factors the role of extension workers, the role of farmer groups, mass media, facilities and infrastructure as well as the analysis used is descriptive analysis, Multiple Linear Regression analysis, Kendal W The results showed that the knowledge was classified as moderate, the persuasion was classified as moderate, the decision was classified as moderate, the implementation was classified as low, the confirmation was classified as moderate. Factors related to the adoption of innovations by farmer group members are age, length of farming, and mass media. to improve the adoption of innovation, counseling is carried out with materials on the implementation of ZPT (growth regulators) and knowledge of ZPT (growth regulators)